Incentive Fees and Mutual Funds - Elton, Edwin J.; Gruber, Martin J.; Blake, Christopher R. (Journal of Finance, 2003)
ABSTRACT This paper examines the effect of incentive fees on the behavior of mutual fund managers. Funds with incentive fees exhibit positive stock selection ability, but a beta less than one results in funds not earning positive fees. From an investor's perspective, positive alphas plus lower expense ratios make incentive‐fee funds attractive. However, incentive‐fee funds take on more risk than non‐incentive‐fee funds, and they increase risk after a period of poor performance. Incentive fees are useful marketing tools, since more new cash flows go into incentive‐fee funds than into non‐incentive‐fee funds, ceteris paribus.